Dietary Practices, Junk Food Consumption and Overweight among Adolescents in Schools of Urban Slums, Bengaluru - Vanitha B; Reddy, Ramakrishna; Ranganath TS; Vishwanatha (National Journal of Community Medicine, 2019)
Introduction: Non-communicable diseases (NCDs) are among the rising trend and are often caused by modifiable risk factors. Ado- lescents are frequent victims due to junk food consumption and un- healthy diet leading to overweight and obesity. A nutritionally ad- equate and balanced diet is essential for optimal growth and devel- opment. Objectives: A cross-sectional study to assess the knowledge, atti- tude and dietary practices among the adolescents of urban slums. Also, to find the association of Body Mass Index (BMI) with fre- quency of junk foods consumption. Materials and methods: 230 adolescents aged 13-15 years in Benga- luru Urban slums were assessed using multi-stage random sam- pling technique and data was collected. Bowl-method was em- ployed to quantify the measurements of foods consumed. Standard precautions were taken to measure height and weight. Chi-square test was used to find association between BMI and frequency of junk food consumption. Results: Mean age of the students was 14.02 (SD 0.96) and majority were in 8th standard (42.2%). 116 (50.4%) of them were boys. Mean BMI of the adolescents was 20.7kg/m2 (SD 3.6) where, 68 (29.6%) of them were underweight, 62 (27%) were overweight and 4 (1.7%) were obese. Only 39% had good knowledge, 71% had favourable attitude and good practice in 31% of adolescents. There was signif- icant association with frequency of junk food consumption and BMI variation. Conclusion: Adolescents had poor knowledge and practice. Over- weight was more prevalent among boys and Underweight in girls. There was significant association with frequency of junk food con- sumption and BMI variation.